Changes in soil microbial communities from exposed rocks to arboreal rhizosphere during vegetation succession in a karst mountainous ecosystem - Ying Li (Taylor & Francis Group, 2021)
To provide information that can support natural vegetation restoration in karst areas, we investigated the change rules of soil microbial communities during vegetation succession from bare rock to arboreal forest using high-throughput sequencing. The results showed that vegetation succession did not cause significant changes in alpha diversity of soil microbial communities. The main bacterial phyla were Proteobacteria, Actinobacteria, and Acidobacteria during vegetation succession. There was a shift from Ascomycota to Basidiomycota during succession, and the relative abundance of Basidiomycota in arboreal rhizosphere soil was the highest; this promoted mycorrhizal formation with the trees and mineral nutrient absorption by the host. Most of the symbiotic networks between soil microorganisms showed cooperative relationships. We propose that the dominant microbes contributed to the biological weathering of limestone and soil evolution under vascular plants. Furthermore, the findings of this study can help improve soil properties by providing insight into how to adjust microbial composition.